Kesesuaian Akad dan Transaksi Digital pada Fintech Syariah dengan Prinsip Hukum Muamalah - Fatimah Salma Azzahra; Azhar Alam; Wardah Yuspin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify and describe the various forms and types of contracts used in Islamic fintech services in Indonesia, and to analyze and assess the level of conformity of contracts and digital transactions in Islamic fintech with the principles of muamalah law according to Islamic teachings. The study used a qualitative literature study method with a normative-theological approach. Data sources were secondary sources collected using library research techniques. Data were considered valid if they met the criteria of credibility, transferability, dependability, and confirmability. Data were analyzed using qualitative descriptive techniques. The results show that Islamic fintech in Indonesia has implemented various Islamic contracts, such as sale and purchase, musyarakah, mudharabah, wakalah bil ujrah, and qardh, which are used according to service characteristics and user needs. In general, the digital transaction mechanisms in Islamic fintech are in line with the principles of muamalah law because they are supported by clear contracts, system transparency, and regulatory oversight that ensures the avoidance of usury, gharar, and other prohibited practices.